Rock 'n' roll - Gish, D.L (World of music, 2005)
Traces the origins of rock and roll music from its beginnings through the end of the 20th century, discussing musical instruments, performers, and styles, such as pop, folk, heavy metal, funk, disco, punk, rap, hip-hop, post-modern, and alternative.